IMPLEMENTASI AKAD MUDHOROBAH PADA KOPERASI SIMPAN PINJAM DAN PEMBIAYAAN SYARIAH BAITUL MAAL WATTAMWIL “BINAMA” SEMARANG - Diah Sasikirana Retno Murniati; Muhammad Junaidi (Jurnal Ius Constituendum, 2017)
ABSTRACTAlthough BMT (Baitul Maal wat Tamwil) has not had legal peotection, but in its principle these BMT institutions have performed their function asintermediary institutions that manage funds from, for and by the society. Theproblem of Bmt is not only limited to the legal legality that protect them, but alsorelated to the law of guarantee. Based on the above background, the writer formulates the purpose ofwriting, namely To know the Implementation of Mudharabah Agreement in KSPSBaitul Maal Wattamwil "Binama" Semarang and to understand the obstacles andsolutions. The method of approach used in this study is the juridical sociologicalapproach. The specification of this study is descriptive analysis, which is expectedto be able to provide detail, systematic, and comprehensive description of allmatters related to the object to be studied. The data used in this study are primarydata and secondary data, i.e data obtained through interviews and librarymaterials collected through bibliographic data, which then analyzed qualitatively. The conclusion of this study is that the Implementation of Mudharabahagreement in KSPS BMT Binama Semarang is in the form of mudharabah savingand mudharabah financing. In the implementation, saving or mudharabah savingcan be implemented smoothly, while mudharabah financing scheme is stilldifficult to be implemented in KSPS BMT Binama because the financing ofmudharabah is difficult to be implemented due to the constraints such as thedifficulty of transparency of mudhorib regarding to the profit obtained, thusinhibiting the purpose of mudharabah financing according to Islamic sharia. Inaddition, KSPS BMT BINAMA in providing financing must be with assurance. Todeal with these obstacles, the solutions implemented by KSPS BMT BINAMA inaccordance with the principle of justice are as follows: 1) Market penetration,that is by recruiting new members and make the old members loyal throughvarious services programs in BMT; 2) Cooperate with sponsorship pattern withother agencies for synergy; 3) Public awareness on sharia saving and loan. 4)Assess prospective members or customers from various aspects. The aspects offinancing are better known as the 5 C's principles.